European Flagship Universities: balancing academic excellence and socio-economic relevance - Background report University of Copenhagen - Kalpazidou Schmidt, Evanthia (CFA Scientific Reports, 2012)
The report is a case study of the University of Copenhagen as a contribution to the Flagship project, which in a comparative perspective analyses the way in which European flagship universities are adapting to a common European governance and policy framework. The universities in Denmark have been subject to far-reaching reforms, where demands on closer interplay with the private sector and dissemination of knowledge to society at large have been central. Universities are therefore expected to find the right balance between academic excellence and socio-economic relevance while having to find their “room to manoeuvre”, managing internal and external conditions in a new national and global framework.